"Us versus Them": is the voice of the community heard when planning communication screening programmes for preschoolers? - Peter VZ; Rea P; Pillay M; Saman Y (Elsevier Ltd. on behalf of The Royal Society for Public Health, 2024)
OBJECTIVES: Community consultation is necessary to ensure the uptake and use of community-based screening intervention to detect early childhood disabilities, as its absence can result in poor service acceptance and usage. To document stakeholders' perspectives regarding planning a community-based communication disorder (an impairment in the ability to receive, send, process and comprehend concepts or verbal, non-verbal and graphic symbol systems) screening programmes for pre-schoolers. STUDY DESIGN: This qualitative research design used purposive and random sampling to recruit 46 participants from eThekwini Municipality, South Africa. These stakeholders consisted of caregivers/parents of children who underwent screening for communication disorders, People who are Deaf, their parents, early childhood development practitioners, health professionals and government officials involved with children with disabilities. All participants were adults aged between 19 and 79 years, with an average age of 39.7 years. METHODS: Data was collected through focus group discussions and individual interviews, which were thematically analysed. RESULTS: The four emergent themes were screening approaches, methods, location and personnel. Service users expected greater access to screening and reliable tests to identify problems by trained personnel at sites within the community. Service providers preferred a targeted approach to screening with parental input. Task shifting and sharing were seen as a solution to address staff shortages and provide services at health facilities, as resource constraints made it challenging to provide outreach services. CONCLUSION: Stakeholder engagement revealed diverging views between service users and providers, with implications for programme provision and uptake. There is a need for ongoing, inclusive discussion to ensure consensus during the planning stage, in order to render services that address issues of equity and accessibility for people with disabilities in marginalised communities.
Keywords: Accessible; Community-based; Design; Equitable; Preschoolers; Screening